The impact of notional defined contribution system (NDC) from the point of view of individual - Švedienė, Milda; Slavickienė, Astrida (Buhalterinės apskaitos teorija ir praktika, 2014)
Retirement benefit plans are the relevant theme in the world and in Lithuania as well. The demographic challenges such as ageing and shrinking labour force cause the problem which usual PAYG system is not able to solve. Whereas this problem is very important in Lithuania simulation of notional defined contribution system is suggested. The influence of new pension system to individuals is analysed in this paper.  The analysis of theoretical works showed that NDC system is defined contribution (DC) system financed as in pay-as-you-go (PAYG) system. This pension scheme is different from others because of it accounting mechanism: contributions of individuals are accumulated on their individual accounts but whereas real capital is not accumulated the balance is notional. All accumulated sum is converted to pension benefit when individuals are at retirement age depending on cohort’s life expectancy. It is said that NDC pension system helps to solve problems such as sensitivity to changes in economic growth, decreasing volume of savings or create a better link between contributions and benefits.  Nevertheless it is recognized that benefit return in NDC pension system is less than in usual defined contribution system.The results of simulation have showed that notional defined contribution system in Lithuania would not be the way out from problems in pension system. The system would be balanced in 30-year period and indexation would be acceptable for individuals but from 2040 interest rate would be reduced by the relevant part of the balance ratio. Depending on the changes in interest rate from 2040 notional capital would be less than all sum of contribution paid and it would negatively impact individuals’ finances. It was found that the more years individuals spend in labour market the bigger capital they accumulate and the bigger benefit get when they are at retirement age. Nevertheless it was noticed that replacement rate would be approximately 25 percent and it would not be adequate for the required use of retirees.
Keywords: notional defined contribution system; pension system; internal return